2014
DOI: 10.1002/mame.201400187
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of Transesterification, Chain Branching and Cross‐Linking in a Biopolyester Commercial Blend upon Reaction with Dicumyl Peroxide in the Melt

Abstract: Aiming at the tuning of thermo‐mechanical features by chemical cross‐linking, a biopolyester commercial blend based on poly(lactic acid) (PLA) with poly(butylene adipate‐co‐terephthalate)(PBAT) (ecovio®T2280, BASF) was processed in Brabender in the presence of dicumyl peroxide (DCP, 0–0.2 wt.‐%). The effect of DCP addition was investigated and rationalized by means of solubility tests and gel content evaluation, as well as rheological, mechanical, and molecular weight analysis of the prepared compounds. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…This indicated that the formed PLA/PBAT blends are not thermodynamically miscible. Similar results were reported by (Signori et al 2015) regarding PLA/PBAT blends containing 75 wt% of PLA.…”
Section: Thermal Propertiessupporting
confidence: 89%
“…This indicated that the formed PLA/PBAT blends are not thermodynamically miscible. Similar results were reported by (Signori et al 2015) regarding PLA/PBAT blends containing 75 wt% of PLA.…”
Section: Thermal Propertiessupporting
confidence: 89%
“…To evaluate the interaction between zeolite and PBAT, FTIR spectra for the membrane containing zeolite Y (PBAT/ZYC10%) and its precursors (ZYNa‐C and PBAT) were obtained (Figure ). Bands referring to PBAT and zeolite Y were both noticed in FTIR spectra of PBAT/ZYC10% sample, as shown in Table . No strong interaction must occur between PBAT and zeolite Y.…”
Section: Resultsmentioning
confidence: 89%
“…For example, impact strength value for pure PLA/PBAT blend was only 60 J/m, while for PLA/ PBAT blends after in-situ compatibilization with DCP was 110 J/m. Signori et al [98] modified commercial aliphatic polyesters blend (based on PLA and PBAT) with trade name Ecovio ® from BASF using variable content (0-0.2 wt%) of dicumyl peroxide. It was found that free radical promoted radical chain branching and cross-linking of PLA/PBAT blends.…”
Section: Aliphatic Polyesters Blendsmentioning
confidence: 99%